2015
DOI: 10.5152/akd.2014.5285
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of association between common genetic variants on chromosome 9p21 and coronary artery disease in Turkish population

Abstract: Objective:Coronary artery disease (CAD), which develops from complex interactions between genetic and enviromental factors, is a leading cause of death worldwide. Based on genome-wide association studies (GWAS), the chromosomal region 9p21 has been identified as the most relevant locus presenting a strong association with CAD in different populations. The aim of the present study was to investigate the association of two SNPs on chromosome 9p21 on susceptibility to CAD and the effect of these SNPs along with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
(76 reference statements)
3
16
0
Order By: Relevance
“…It has been found that chromosome 1p31 locus is specific to peripheral arterial occlusive disease, which is diagnosed angiographically and/or surgically. Rs1333049 on chromosome 9p21 was not only associated with coronary artery disease (CAD) susceptibility, but also associated with PAD, which indicated that CAD and PAD might have a common genetic basis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that chromosome 1p31 locus is specific to peripheral arterial occlusive disease, which is diagnosed angiographically and/or surgically. Rs1333049 on chromosome 9p21 was not only associated with coronary artery disease (CAD) susceptibility, but also associated with PAD, which indicated that CAD and PAD might have a common genetic basis.…”
Section: Introductionmentioning
confidence: 99%
“…Cakmak et al. found rs2383207 and rs1333049 were significantly associated with the risk and severity of CAD in the Turkish population (Çakmak et al., ). However, several studies failed to demonstrate a significant association between the 9p21 genotypes and CAD severity by Gensini score in Asian populations (Hinohara et al., ; Hiura et al., ; Shen et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In a very recent study performed by Çakmak et al, 29) the two SNPs of rs2383207 and rs1333049 at the 9p21 chromosome were evaluated in 220 patients with CAD in a Turkish population. Significant differences were seen in frequencies of rs2383207 and rs1333049 variants between CAD patients and healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Our study population was wider and patient selection showed important discrepancies between the two studies. Çakmak et al 29) did not include patients older than 55 years in male -and 65 years in female patients. However, these gene polymorphisms are particularly expected to be related with premature atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%